Salivary microbiome composition changes after bariatric surgery - Džunková, Mária; Lipták, Róbert; Vlková, Barbora; Gardlík, Roman; Čierny, Michal; Moya, Andrés; Celec, Peter (Scientific reports, 2020)
Recent studies show that the salivary microbiome in subjects with obesity differ from those without obesity, but the mechanism of interaction between the salivary microbiome composition and body weight is unclear. Herein we investigate this relation by analyzing saliva samples from 35 adult patients with obesity undergoing bariatric surgery. Our aim was to describe salivary microbiome changes during body weight loss on an individual-specific level, and to elucidate the effect of bariatric surgery on the salivary microbiome which has not been studied before. Analysis of samples collected before and 1 day after surgery, as well as 3 and 12 months after surgery, showed that the salivary microbiome changed in all study participants, but these changes were heterogeneous. In the majority of participants proportions of Gemella species , Granulicatella elegans, Porphyromonas pasteri, Prevotella nanceiensis and Streptococcus oralis decreased, while Veillonella species , Megasphaera micronuciformis and Prevotella saliva increased. Nevertheless, we found participants deviating from this general trend which suggests that a variety of individual-specific factors influence the salivary microbiome composition more effectively than the body weight dynamics alone. The observed microbiome alternations could be related to dietary changes. Therefore, further studies should focus on association with altered taste preferences and potential oral health consequences.